Holocaust Heritage : inquiries into European historical cultures - Karlsson, Klas-Göran Hrsg; Echoes of the Holocaust; The Holocaust and the European Historical Culture (Sekel, 2004)
This book is the second collection of reports from "The Holocaust and European Historical Cultur". The title of the first collection is "Echoes of the Holocaust"